Clinical disease and host response of nursery pigs following challenge with emerging and re-emerging swine viruses - Niederwerder, Megan C. (Kansas State University, 2015)
Emerging viral diseases cause significant and widespread economic losses to U.S. swine production. Over the last 25 years, porcine reproductive and respiratory syndrome virus (PRRSV), porcine circovirus type 2 (PCV2) and porcine epidemic diarrhea virus (PEDV) have emerged or re-emerged, costing the industry billions through increased mortality and clinical or subclinical reductions in growth. Nursery pigs are greatly affected by these viruses due to high susceptibility to primary and secondary infections after weaning. However, clinical disease occurs in only a subpopulation of infected pigs and can vary drastically from sudden death to poor growth performance. This thesis documents a series of 4 studies where nursery pigs were challenged with either PRRSV/PCV2 or PEDV; the associations between clinical outcome and several factors affecting viral pathogenesis were investigated. In the first study, the administration of PRRS modified live virus vaccine prior to co-challenge with PRRSV/PCV2 was shown to protect against PRRS but enhance PCV2 replication and pathogenesis. This study provides insight into the role that PRRS vaccination has in both the control and potentiation of clinical disease. In the second study, microbial populations were compared between pigs with the best and worst clinical outcome following PRRSV/PCV2 co-infection. Increased fecal microbiome diversity was associated with improved clinical outcome; however, worst clinical outcome pigs had prolonged and greater virus replication, highlighting the host response to viral challenge as a primary determinant of clinical outcome. In the third study, 13 clinical phenotypes were compiled for >450 pigs after PRRSV/PCV2 co-infection. Duration of dyspnea and the presence of muscle wasting had the strongest associations with reduced weight gain. This study highlights the opportunity to improve animal welfare and production through improvements in clinical health. In the fourth study, clinical disease was mild to moderate and occurred within the first week after pigs were challenged with PEDV. However, PEDV was detected weeks after clinical disease had resolved and may implicate nursery pigs as an important source of viral carriage and transmission. Overall, the goal of this thesis was to develop models for understanding the impact of emerging and re-emerging viruses to improve recognition and control of disease.
Keywords: Porcine reproductive and respiratory syndrome virus; Porcine circovirus type 2; Porcine epidemic diarrhea virus; Clinical disease; Viral pathogenesis; Nursery pigs; Veterinary Medicine (0778); Virology (0720)